Aplikasi Pencarian Rekan dan Tempat Singgah saat Touring Berbasis Android - Glenn Nazari; Ester Lumba (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to produce a peer search application and a place where Android-based touring. This application was created to find partners and places to stop online for people who want to do touring. Users who will be touring can see the information of other users who want to touring to the same destination, then the user can make a partner search and respond to other users' peer searches. Users can also search for a place to stay and respond to a search for other users. Researchers used the Rational Unified Process (RUP) development method by using the Unified Modeling Language (UML) system modeling. The development of this application uses Android studio software using the Java Programming Language, XML, PHP, and using the MySQ database. The final results obtained from this study are peer search applications and places where touring based on Android.